The role of laparoscopic surgery in the surgical management of recurrent liver malignancies: A systematic review and meta-analysis - Lv, Tian-Run; Hu, Hai-Jie; Ma, Wen-Jie; Hu, Ya-Fei; Dai, Yu-Shi; Li, Fu-Yu (Frontiers in Surgery, 2023)
Abstract Objective: To evaluate the efficiency of laparoscopic surgery in treating recurrent liver tumors versus conventional open surgery. Methods: Database searching was conducted in PubMed, the Cochrane Library and EMBASE. RevMan5.3 software and Stata 13.0 software were applied in statistical analyses. Results: A total of fourteen studies were finally included with 1284 patients receiving LRH and 2254 with ORH. LRH was associated with less intraoperative hemorrhage, a higher R0 resection rate, a lower incidence of Pringle Maneuver, a lower incidence of postoperative morbidities, a better overall survival and an enhanced postoperative recovery versus ORH. Patients receiving LRH shared similar operative time, tumor number and disease-free survival as those with ORH. However, tumor size was relatively larger in patients receiving ORH and major hepatectomy, anatomic hepatectomy were rarely performed in patients with LRH. Additional analyses between LRH and laparoscopic primary hepatectomy revealed less intraoperative blood loss in patients with LRH. Conclusion: LRH is safe and feasible with more favorable peri-operative outcomes and faster postoperative recovery. However, it is only applicable for some highly-selected cases not requiring complex surgical procedures. Future larger well-designed studies are expected for further validation